2020
DOI: 10.1002/aic.17077
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thickness and wax content of wax deposits in polyethylene pipe using a flow loop

Abstract: In this study, the thickness and wax content of wax deposits were found to be thinner and lower in the polyethylene (PE) pipe than in the stainless steel (SS) pipe using a flow loop apparatus. The diffusivity of wax, radial thermal gradient, and wax precipitation rate in the PE and SS pipes were calculated and compared. It was found the diffusivity of wax in the PE pipe was higher and tended to enhance the wax deposition in the PE pipe, while the radial thermal gradient and wax precipitation rate were lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Collectively, it seems reasonable to accept that there is a slight difference in deposition, given that the PTFE deposit is marginally larger in all cases. These observed material effects on deposition are much smaller in magnitude compared to those reported in previous work. Given the fact that none of the previous work attempted to maintain the same surface temperature when different surface materials were used, it is likely that the observed large differences in deposition from previous work were mainly caused by thermal effects rather than material effects.…”
Section: Results and Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Collectively, it seems reasonable to accept that there is a slight difference in deposition, given that the PTFE deposit is marginally larger in all cases. These observed material effects on deposition are much smaller in magnitude compared to those reported in previous work. Given the fact that none of the previous work attempted to maintain the same surface temperature when different surface materials were used, it is likely that the observed large differences in deposition from previous work were mainly caused by thermal effects rather than material effects.…”
Section: Results and Discussionmentioning
confidence: 72%
“…Li et al explored surface effects by comparing polyethylene (PE) and steel test sections in a flow loop. , Their initial experiments showed that the PE generated thinner deposits with lower wax content. In their paper presenting these results, they conclude that these results are mainly caused by the lower thermal conductivity of PE as compared to steel, which generates a decreased thermal gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, only a few experiments about nonmetallic pipelines influencing wax molecule movement progress, especially PE pipeline, were conducted in the past time 21 . At the beginning period, nonmetallic coated cold finger is one of the widely used approaches to carry out wax deposition experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, only a few experiments about nonmetallic pipelines influencing wax molecule movement progress, especially PE pipeline, were conducted in the past time. 21 At the beginning period, nonmetallic coated cold finger is one of the widely used approaches to carry out wax deposition experiments. Jorda et al explore the difference between several cold finger devices with two kinds of nonmetallic coated and steel coated respectively during wax deposition experiments.…”
Section: Introductionmentioning
confidence: 99%